2012
DOI: 10.1111/ajo.12010
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of preconception care in women with pregestational diabetes 
in Western Australia

Abstract: This study investigated the level of awareness of the availability of preconception care in a tertiary obstetric hospital for women with type 1 and 2 diabetes, the willingness of these women to attend for preconception counselling and the barriers that may impact upon access to preconception care in Western Australia. The results show greater effort is needed to improve the awareness of women about the importance of preconception care and their willingness to attend the clinic. Access to consistent preconcepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 6 publications
1
48
1
Order By: Relevance
“…In a Western Australian prospective study of pregnant women with pre-existing diabetes, a significant proportion (45%) of pregnancies were also unplanned and only 8% of women had attended preconception care [39]. A large retrospective cohort study in the USA found that women with diabetes were less likely than women without a chronic condition to have documented receipt of any contraceptive counselling, prescriptions, or services [40], showing that contraception-an important aspect of timed conception-is often overlooked in women with complex medical needs.…”
Section: Discussionmentioning
confidence: 99%
“…In a Western Australian prospective study of pregnant women with pre-existing diabetes, a significant proportion (45%) of pregnancies were also unplanned and only 8% of women had attended preconception care [39]. A large retrospective cohort study in the USA found that women with diabetes were less likely than women without a chronic condition to have documented receipt of any contraceptive counselling, prescriptions, or services [40], showing that contraception-an important aspect of timed conception-is often overlooked in women with complex medical needs.…”
Section: Discussionmentioning
confidence: 99%
“…Women are also encouraged to achieve a target glycosylated level of hemoglobin (HbA1c; average blood glucose level over the past 2-3 months) of <7% before and during the first trimester of pregnancy to reduce obstetric risks [29,36,38-41]. However, less than 50% of women with DM receive PCC advice [34,43,44] with fragmented and suboptimal services being reported [45-47]. As a result, women with DM have insufficient knowledge of the risks associated with pregnancy to themselves or their baby [12,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Fetal macrosomia was observed at a higher rate with type 2 diabetes, that is, in 68.8% compared with 29.4% in type 1 diabetes and 16.8% in gestational diabetes. A strong association between fetal macrosomia and other adverse outcomes such as caesarean section, shoulder dystocia and birth trauma was also evident in this study.…”
Section: Resultsmentioning
confidence: 99%